Respuesta :
Given a = 3 and b = - 8 ,
= > 2b² - 4a + 4a²
= > 2( - 8 )² - 4( 3 ) + 4( 3 )²
= > 2( 64 ) - 4( 3 ) + 4( 9 )
= > 128 - 12 + 36
= > 116 + 36
= > 152
[tex] \: [/tex]
= > 2b² - 4a + 4a²
= > 2( - 8 )² - 4( 3 ) + 4( 3 )²
= > 2( 64 ) - 4( 3 ) + 4( 9 )
= > 128 - 12 + 36
= > 116 + 36
= > 152
[tex] \: [/tex]
Hey there!!
The given equation : 2b² - 4a + 4a²
Where, a = 3 and b = -8
Now, we will have to substitute these values in the equation given above
2 ( - 8 )² - 4 ( 3 ) + 4 ( 3 ) ²
( -8 )² = 64
Because -8 × -8 = 64 . As ( - ) × ( - ) = ( + )
negative × negative = positive
Now, moving on
2 ( 64 ) - 4 ( 3 ) + 4 ( 9 )
128 - 12 + 36
116 + 36